STUDY ON GAS CHROMATOGRAPHY AND MASS SPECTROSCOPY ANALYSIS, ANTIOXIDANT, AND NUTRITIVE PROPERTIES OF AERVA LANATA (L.) JUSS. COLLECTED FROM SELECTED REGIONS OF SHIMOGA, KARNATAKA, INDIA - PRASAD YADAV, VENAKTESH; R, ASHWATHANARAYANA; MS, PADMASHREE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Aerva lanata (L.) Juss., the plant ethanolic extract was subjected to gas chromatography and mass spectroscopy, antioxidant, and nutritive experiment using standard methods. Methods: Antioxidant experiment is done using 2, 2‑diphenyl‑1‑picrylhydrazyl, 2, 2‑azobis‑3‑ethylbenthiozoline‑6‑sulfonic acid, superoxide radical scavenging, hydroxy radical scavenging, and metal‑chelating assays. Nutritive value is performed by double acid digestion followed by atomic absorption spectroscopy. Results: Antioxidant experiment revealed that A. lanata (L.) Juss. the plant ethanolic extract has good medicinal compounds exhibits excellent antioxidant activity in all tested experiments, but comparably less with the standards used. From nutritive value experiment, it is revealed that A. lanata (L.) Juss the plant has high iron content with rich macro‑ and micro‑nutrients. Conclusion: A. lanata (L.) Juss. could be exploited as a valuable source of antioxidant agent enriching with nutrients.